The influence of work environment and work discipline through motivation on employee performance in perumda tirta manuntung balikpapan city - Amalia, Putri; Hadiyatno, Didik; Cahyaning Putri, Rahajeng (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2025)
The study intends to explore the interaction between work environment and work discipline on employee performance in Perumda Tirta Manuntung, Balikpapan City, where work motivation serves as the mediating variable. Employee performance is a particular concern due to its importance in maintaining clean water services. This research applies quantitative analysis with an explanation of the design and involves 104 permanent employees chosen by purposive sampling. The data were collected through the use of a Likert-scale questionnaire and analyzed by means of Structural Equation Modeling (SEM) in the Partial Least Square (PLS) approach. The results show that the work environment and work discipline affect work motivation and employee performance directly and indirectly (through motivation as a mediator). A favorable work environment improves comfort and enthusiasm, and a workplace that enforces discipline improves commitment and efficiency. Work motivation has a strong binding role to these relationships. Thus, it is concluded that to optimize employee performance, Perumda Tirta Manuntung should create an enabling environment for work, practice a work discipline that is fair to all, and enhance work motivation through a reward system. Recommendations include the need to improve work conditions like physical facilities, promote better interpersonal communication, and conduct some training for the improvement of disciplines and motivation. Keywords: employee performance; work discipline; work environment; work motivation